Communicate to win - Denny, Richard (London Kogan Page, 2009)
Communicate to Win is full of sound, practical advice on every aspect of business and personal communication, such as how to: encourage people to like you, understand what motivates people, use the telephone effectively, excel at one-on-one conversation, develop your emotional intelligence, master a good writing style and give a great public presentation.
Copyright; Table of contents; About the Author; Introduction; Part 1 Communication Skills; Ch 1 The Importance of Communication; Ch 2 Interpersonal Communication; Ch 3 Helping People to Like You; Ch 4 Dealing with People; Ch 5 Giving and Taking Instruction Effectively; Ch 6 Body Language; Ch 7 Written Communication; Ch 8 Telephone Communication; Ch 9 Meetings; Part 2 Presenting to Win; Ch 10 Presentation Skills; Ch 11 Nervous Tension; Ch 12 Preparation; Ch 13 Content; Ch 14 Your Audience; Ch 15 Visual Aids; Ch 16 Your Appearance & Attitude; Ch 17 Delivery; Ch 18 Develop Good Habits.
Cover title: Communicate to win : learn the secrets of successful communication and presentation. Description based on print version record.
Electronic reproduction.
Keywords: Business communication; Communication; Business presentations; Success in business; Electronic books